Trade and the skilled-unskilled wage gap in a model with differentiated goods - Thierfelder, Karen; Robinson, Sherman (International Food Policy Research Institute, 2002)
There is a continuing debate about the role of changes in trade on the evolution of relative wages particularly the skilled-unskilled wage gap. In the 1980's, the wage gap widened considerably in the United States, and there was an active literature on the roles of trade, technology, and changes in labor supplies, particularly due to migration and education, in explaining these changes. The empirical models used to analyze the links fall into two broad groups: (1) partial-equilibrium models of the labor market, focusing on changes in the supply and demand of labor by skill category, and (2) general equilibrium trade models linking domestic factor returns to changes in world prices and the composition of trade....In this paper, we present a theoretical model that can capture many of the differences between the approaches of trade and labor economists.-- from Authors' Introduction.